Nonlinear modal equations for a levitating drop - Chernova, M.O.; Lukovsky, I.A. (Нелінійні коливання, 2012)
Based on variational method, the paper derives nonlinear modal equations describing the dynamics of a levitating drop. Using these equations, we construct an asymptotic modal theory for axisymmetric drop oscillations. We consider nonlinear free oscillations of the drop with the frequency close to the lowest natural frequency, the results are compared with experimental data and numerical results obtained byother authors.